Respuesta :
Answer:
x = -3
Step-by-step explanation:
Step 1: Write out equation
6 - 4x = 6x - 8x + 12
Step 2: Combine like terms (x)
6 - 4x = -2x + 12
Step 3: Add 4x on both sides
6 = 2x + 12
Step 4: Subtract 12 on both sides
-6 = 2x
Step 5: Divide both sides by 2
-3 = x
Step 6: Rewrite
x = -3
Answer:
The answer is x= -3
Step-by-step explanation:
6 - 4x = 6x - 8x + 12
First, add like terms. (6x-8x)
6-4x=-2x+12
Then "add" 4x to both sides.
6=2x+12
Then subtract 12 from both sides.
-6=2x
The final step is to divide. Divide 2 from both.
Your answer is x= -3
I hope this helps!!!